Detections of Screw Penetration during Volar Plating for Distal Radius Fractures - Cha, Soo Min; Shin, Hyun Dae (Journal of Wrist Surgery, 2017)
Background We evaluated the detection for screw penetration on the dorsal cortex of the radius in serial oblique, dorsal tangential, and radial groove radiographic views in volar plating fixation. Materials and Methods Eight screw positions were set in each of the four cadaveric radii. Screw 1 was placed in the styloid subregion, whereas screws 2 and 3 were placed just proximal to the styloid and were defined for the radial region of the radius. Screws 4 (distal to the extensor pollicis longus [EPL] groove), 5 (the distal half of the groove), and 6 (the proximal half of the groove) were placed in the central region of the radius. Screws 7 (just medial to the groove) and 8 (sigmoid notch subregion) were positioned in the ulnar region of the radius. The screws were overlengthened by 1 and 2 mm and were evaluated in three radiographic views. Results Penetrations in the radial region were fully visible in supinated oblique views with 1- and 2-mm overlengthened screws. The penetration of screw 4 was clearly observable over a considerable range of views. However, the 1-mm penetration of screw 5 was not detectable at any angle of projection. Detection of the ulnar region screw was the most difficult among the three regions with oblique views. In the dorsal tangential view, the 1-mm penetration of screw 4 was not observed in any of the four radii, but the penetration of screw 5 was detectable in all the radii. The screws 2, 3, 5, 7, and 8 were readily detectable. The screw 4 was barely seen in the radial groove view, while the screws 5 and 6 were readily detectable. Conclusion/Clinical Relevance Appropriate combinations of these well-known radiological views are essential for the overall detection of penetrated screws during plating in distal radius fractures.
Keywords: screw perforation; volar plating; oblique view; dorsal tangential view; radial groove view